2021
DOI: 10.25165/j.ijabe.20211401.5477
|View full text |Cite
|
Sign up to set email alerts
|

Operation power consumption and verification tests of a trenching device for orchards in Xinjiang based on discrete element

Abstract: According to the agronomic requirements of orchard planting pattern and fertilization in Xinjiang, the soil particle models and a soil-trenching device interaction model were established by using discrete element simulation software in order to find out the law of influence of structure parameters and working parameters on the operation power consumption of a segmented cutting trenching device; moreover, its cutting process was simulated according to the response surface test design. According to the results o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
(7 reference statements)
0
6
0
Order By: Relevance
“…When a complete set of trenching operations is completed, its motion path is a cycloid 33 .In addition to the physical characteristics of the soil particles, the factors that affect the soil cutting by the trenching cutter head in this movement process should also include the rotation speed of the cutter head, the positive and negative rotation speed and the forward speed of the device. In order to study the movement state of the trenching operation, according to the previous research results and the research basis 34 , the EDEM2020 software is used to establish the soil-cutter head interaction model of the coordinate system with the cutter head rotation center as the origin (as shown in Fig 2). The forward speed and rotational speed of the cutter head are defined consistent with the test.…”
Section: Establishment and Analysis Of Tool Motion Equationmentioning
confidence: 99%
“…When a complete set of trenching operations is completed, its motion path is a cycloid 33 .In addition to the physical characteristics of the soil particles, the factors that affect the soil cutting by the trenching cutter head in this movement process should also include the rotation speed of the cutter head, the positive and negative rotation speed and the forward speed of the device. In order to study the movement state of the trenching operation, according to the previous research results and the research basis 34 , the EDEM2020 software is used to establish the soil-cutter head interaction model of the coordinate system with the cutter head rotation center as the origin (as shown in Fig 2). The forward speed and rotational speed of the cutter head are defined consistent with the test.…”
Section: Establishment and Analysis Of Tool Motion Equationmentioning
confidence: 99%
“…The variety of reed was unknown because it grows wild, the reeds were 3000-4500 mm tall, the bottom diameter of reeds was 12-16 mm, and the water content of reed stalks was 41.3%-56.5%. 2 and conveying rate Y 3 as the cutting and conveying indexes, and a 3-factor, 3-level orthogonal test was carried out with a total of 17 groups and 5 repetitions at the center point [24][25][26][27] . The test factors and levels are listed in Table 2.…”
Section: Test Condition and Test Planmentioning
confidence: 99%
“…The other test parameters were blade length, 120 mm and horizontal distance between the cutting and clamping point, 64 mm. With the failure rate Y 1 , cutting efficiency Y2 and conveying rate Y 3 as the cutting and conveying indexes, and a 3-factor, 3-level orthogonal test was carried out with a total of 17 groups and 5 repetitions at the center point[24][25][26][27] . The test factors and levels are listed in Table2.…”
mentioning
confidence: 99%
“…Ma et al [ 14 ] conducted a study on the impact of forward speed, disc speed, and disc combination on the operational power consumption of a segmented furrow-opening device. They observed that the influence on furrow-opening operational power consumption follows the order from most to least significant: forward speed, disc combination, and disc speed.…”
Section: Introductionmentioning
confidence: 99%